2016
DOI: 10.1111/jmg.12193
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupled U/Pb and REE response in zircon during the transformation of eclogite to mafic and intermediate granulite (Blanský les, Bohemian Massif)

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 92 publications
(185 reference statements)
0
25
0
Order By: Relevance
“…The long residence in the deep crustal level and presence of a melt phase during metamorphism would promote the overgrowth or recrystallization of zircon grains (Rubatto et al ., ; Hermann et al ., ; Rubatto & Hermann, ; Baldwin & Brown, ; Štípská et al ., ). Another favourable factor involves metamorphic temperature.…”
Section: Discussionmentioning
confidence: 97%
“…The long residence in the deep crustal level and presence of a melt phase during metamorphism would promote the overgrowth or recrystallization of zircon grains (Rubatto et al ., ; Hermann et al ., ; Rubatto & Hermann, ; Baldwin & Brown, ; Štípská et al ., ). Another favourable factor involves metamorphic temperature.…”
Section: Discussionmentioning
confidence: 97%
“…(). These methods have been used to great effect in a number of studies where the range of zircon and garnet chemistry and morphologies are relatively simple (Clark et al., , ; Gauthiez‐Putallaz, Rubatto, & Hermann, ; Hermann & Rubatto, ; Kotková & Harley, ; Kotková, Whitehouse, Schaltegger, & D'Abzac, ; Kylander‐Clark & Hacker, ; MacDonald et al., ; Štípská et al., ). The utility of these techniques in visualizing equilibrium relationships in terranes that have experienced multiple episodes or protracted durations of metamorphism becomes increasingly complex as zircon undergoes varying degrees of recrystallization, re‐equilibration and neocrystallization.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship has been calibrated from natural mineral pairs (Buick, Hermann, Williams, Gibson, & Rubatto, ; Hermann & Rubatto, ; Hokada & Harley, ; Whitehouse & Platt, ) and experiments (Rubatto & Hermann, ; Taylor, Harley, et al., ). A number of studies have demonstrated that the zircon–garnet relationship can withstand long durations of metamorphism at high temperature (Clark, Collins, Santosh, Taylor, & Wade, ; Harley & Nandakumar, ; Hermann & Rubatto, ; Kelly & Harley, ; Štípská, Powell, Hacker, Holder, & Kylander‐Clark, ; Taylor, Clark, Johnson, Santosh, & Collins, ), further establishing the utility of zircon–garnet relationships in interrogating the evolution of metamorphic terranes. The recently established ability to rapidly acquire in situ isotopic and trace elemental data sets through techniques such as laser ablation split stream petrochronology means that large coupled geochronological–geochemical data sets can be applied to understanding high‐ T events (Horton et al., ; Kylander‐Clark, Hacker, & Cottle, ; Shaffer, Hacker, Ratschbacher, & Kylander‐Clark, ).…”
Section: Introductionmentioning
confidence: 97%
“…Either the zircon grains were not in equilibrium with the other phases in the rock (possibly due to their position in the now‐former osumilite) or they did not grow/recrystallize at UHT. A similar lack of compositional equilibrium during resetting of zircon U–Pb dates has been documented in the granulites of Blanský Les in the Bohemian Massif (Štípská, Powell, Hacker, Holder, & Kylander‐Clark, ). All monazite from this sample is isotopically homogeneous: 561 ± 6 Ma (Figure h).…”
Section: U–pb Laser‐ablation‐split‐stream Icp‐ms Monazite and Zircon mentioning
confidence: 99%